A Comparison of Group Anger Management Treatments for Combat Veterans With PTSD: Results From a Quasi-Experimental Trial - Van Voorhees, Elizabeth E. (Journal of interpersonal violence, 2021)
Difficulty controlling anger is a significant concern among combat veterans with posttraumatic stress disorder (PTSD), yet few controlled studies have examined the efficacy of anger treatments for this population. This study examined the effects of a group cognitive behavioral therapy (CBT) intervention compared with a group present-centered therapy (PCT) control condition in male and female combat veterans with PTSD. Thirty-six combat veterans with PTSD and anger difficulties began group treatment (CBT, n = 19; PCT, n = 17). Separate multilevel models of self-rated anger, PTSD symptoms, and disability were conducted using data from baseline, each of 12 treatment sessions, posttreatment, and 3- and 6-month follow-up time points. Significant decreases in anger and PTSD symptoms were observed over time, but no significant differences between CBT and PCT were observed on these outcomes. A significant interaction of therapy by time favoring the PCT condition was observed on disability scores. Gender differences were observed in dropout rates (i.e., 100% of female participants dropped out of CBT). Findings suggest that both CBT and PCT group therapy may be effective in reducing anger in combat veterans with PTSD. Results also highlight potential gender differences in response to group anger treatment.